2014
DOI: 10.1128/jcm.01352-14
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Diversity in Enterocytozoon bieneusi Isolates from Dogs and Cats in China: Host Specificity and Public Health Implications

Abstract: cTo explore the genetic diversity, host specificity, and zoonotic potential of Enterocytozoon bieneusi, feces from 348 stray and pet dogs and 96 pet cats from different locations in China were examined by internal transcribed spacer (ITS)-based PCR. E. bieneusi was detected in 15.5% of the dogs, including 20.5% of stray dogs and 11.7% of pet dogs, and in 11.5% of the pet cats. Higher infection rates were recorded in the >2-year and the 1-to 2-year age groups in dogs and cats, respectively. Altogether, 24 genot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

20
86
3

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(109 citation statements)
references
References 32 publications
20
86
3
Order By: Relevance
“…can cause severe generalised encephalitozoonosis or cataracts and uveitis in cats, these zoonotic agents are probably relatively rare, as evidenced by low seroprevalence (2%) in healthy cats (Buyukmihci et al 1977, Hsu et al 2011, Rebel-Bauder et al 2011). Whereas 13 genotypes of E. bieneusi have been reported in cats (Karim et al 2014), we detected only genotype D, which is one of the most frequently reported genotypes (Santín et al 2006, Xu et al 2016. In contrast to previous surveys (Dengjel et al 2001, Xu et al 2016), we did not find E. bieneusi in pet cats.…”
contrasting
confidence: 56%
“…can cause severe generalised encephalitozoonosis or cataracts and uveitis in cats, these zoonotic agents are probably relatively rare, as evidenced by low seroprevalence (2%) in healthy cats (Buyukmihci et al 1977, Hsu et al 2011, Rebel-Bauder et al 2011). Whereas 13 genotypes of E. bieneusi have been reported in cats (Karim et al 2014), we detected only genotype D, which is one of the most frequently reported genotypes (Santín et al 2006, Xu et al 2016. In contrast to previous surveys (Dengjel et al 2001, Xu et al 2016), we did not find E. bieneusi in pet cats.…”
contrasting
confidence: 56%
“…Despite repeated reports of E. bieneusi in humans and domestic and wild animals in China, the transmission routes of human microsporidiosis remain unclear (1,(8)(9)(10)(13)(14)(15). Contact with pigs was considered a risk factor for acquisition of E. bieneusi genotype EbpC in HIV ϩ farmers in Henan (8).…”
mentioning
confidence: 99%
“…It is worth noting that genotype D has been identified in humans as well as various animals, and is considered a zoonotic genotype (Yang et al 2015). The other zoonotic genotypes (PigEBITS5, EbpA, Peru8, Type IV) were also detected in animals in Zhengzhou (Karim et al 2014a, Qi et al 2015. Beside these, the remaining genotypes of positive samples (22/46) belonged to the potential zoonotic group (group 2).…”
Section: Discussionmentioning
confidence: 99%
“…According to previous reports from Zhengzhou (Karim et al 2014a, Qi et al 2015, E. bieneusi in wastewater mainly originated from animals faeces The ITS tree was rooted with GenBank sequence AY237213 WL15 (an E. bieneusi genotype from group 3). The subgroups in group 1 were named according to Thellier and Breton (2008) and Karim et al (2015).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation